ALTERNATIVES TO MEAT PROTEIN - Ангельська, Світлана (SWorldJournal, 2022)
In the past, non-muscle proteins in meat products were used mainly for technological or economic reasons. The addition of milk proteins to canned sausages or the use of blood plasma are good examples of the use of non-muscle proteins to give products the